2009
DOI: 10.1038/ja.2009.93
|View full text |Cite
|
Sign up to set email alerts
|

Screening and evaluation of new inhibitors of hepatic glucose production

Abstract: In the course of our screening program for inhibitors of hepatic glucose production in rat hepatoma H4IIE-C3 cells, which were used as model liver cells, five naphtoquinone derivatives-javanicin, solaniol, 9-O-methylfusarubin, 5,10-dihydroxy-1,7-dimethoxy-3-methyl-1H-naphtho[2,3-c]pyran-6,9-dione, 9-O-methylbostrycoidin-and vanillin were selected from our natural product library. These naphtoquinone derivatives inhibited hepatic glucose production at IC 50 values of 3.8-29 lM, but showed cytotoxicity against h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Compound 1 was previously reported as a phytotoxin, cytotoxin against human cancer cells, a anti-parasitic agent against Trichomonas vaginalis, and an anti-tuberculosis agent [20][21][22][23]. Compound 4 was known with the hepatic glucose production inhibiting activity and cytotoxicity [24]. Compound 5 was also reported to have cytotoxicity and antibacterial activity as well as anti-parasitic activity and hepatic glucose production inhibiting activity [22,25,26].…”
Section: Biological Activities Of Isolated Compoundsmentioning
confidence: 99%
“…Compound 1 was previously reported as a phytotoxin, cytotoxin against human cancer cells, a anti-parasitic agent against Trichomonas vaginalis, and an anti-tuberculosis agent [20][21][22][23]. Compound 4 was known with the hepatic glucose production inhibiting activity and cytotoxicity [24]. Compound 5 was also reported to have cytotoxicity and antibacterial activity as well as anti-parasitic activity and hepatic glucose production inhibiting activity [22,25,26].…”
Section: Biological Activities Of Isolated Compoundsmentioning
confidence: 99%
“…Early studies described the isolation of 8- O -methylbostrycoidin and showed its cytotoxicity against several mammalian cell lines, including rat hepatoma, Madin Darby canine kidney and Chinese hamster ovary [ 6 ]. Later, Hashimoto again observed the low cytotoxicity against the rat hepatoma cell line, but observed a strong ability to inhibit hepatic glucose production [ 7 ]. More recently, 8- O -methylbostrycoidin has been evaluated for cytotoxicity to a number of human cancer cell lines and has been shown to strongly inhibit α-acetylcholine esterase [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…It showed phytotoxic activity against wheat, bean, corn and tobacco plants at different concentrations and antineoplastic effects on ras transformed liver epithelial cells [ 26 ]. Finally, compound 1 inhibited hepatic glucose production at an IC 50 value of 4.8 μM and showed cytotoxicity against hepatic cells after incubation for 48 h [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…BA-10763 [ 27 ]. In addition, 2 displayed remarkable inhibiting action against α-acetylcholinesterase (AChE) with an IC 50 value of 6.71 μM [ 34 ], inhibited hepatic glucose production at an IC 50 value of 30 μM, and showed weak cytotoxicity against hepatic cells after incubation for 48h [ 33 ]. It also showed bactericidal activity against some Gram+ bacteria, but it has never been tested for phytotoxic activity.…”
Section: Resultsmentioning
confidence: 99%